Feasibility of a simultaneously integrated boost concept for hypofractionated stereotactic radiotherapy of unresected brain metastases - Christine Kornhuber; Stephan Ensminger; Patrick Hübsch; Martin Janich; Chris Andre Leucht; Dirk Vordermark; Christian T. Dietzel (Radiation Oncology, 2023)
Abstract Background In stereotactic radiotherapy, dose is prescribed to an isodose surrounding the planning target volume (PTV). However, the desired dose inhomogeneity inside the PTV leaves the specific dose distribution to the gross tumor volume (GTV) unspecified. A simultaneously integrated boost (SIB) to the GTV could solve this shortcoming. In a retrospective planning study with 20 unresected brain metastases, a SIB approach was tested against the classical prescription. Methods For all metastases, the GTV was isotropically enlarged by 3 mm to a PTV. Two plans were generated, one according to the classical 80% concept with 5 times 7 Gy prescribed (on D2%) to the 80% PTV surrounding isodose (with D98%(PTV) ≥ 35 Gy), and the other one following a SIB concept with 5 times 8.5 Gy average GTV dose and with D98%(PTV) ≥ 35 Gy as additional requirement. Plan pairs were compared in terms of homogeneity inside GTV, high dose in PTV rim around GTV, and dose conformity and gradients around PTV using Wilcoxon matched pairs signed rank test. Results The SIB concept was superior to the classical 80% concept concerning dose homogeneity inside GTV: Heterogeneity index of GTV was in the SIB concept (median 0.0513, range 0.0397–0.0757) significantly (p = 0.001) lower than in the 80% concept (median 0.0894, range 0.0447–0.1872). Dose gradients around PTV were not inferior. The other examined measures were comparable. Conclusion Our stereotactic SIB concept better defines the dose distribution inside PTV and can be considered for clinical use.